“Cognitive Peer Coaching” - a workplace-based faculty development approach for problem- based learning facilitators: a qualitative study - Madeeha Rehan ,; Rahila Yasmeen, (Journal of the Pakistan Medical Association, 2020)
Abstract Objective: To explore the factors affecting the learning process of novice PBL facilitators trained through “Cognitive Peer Coaching”. Method: A qualitative study of phenomenological design was conducted. Total 15 PBL facilitators, five experts and ten novices were selected and were given orientation about cognitive peer coaching through workshops. Novice facilitators were trained by experts through cognitive peer coaching cycle comprising of preobservation, observation and post observation phase following socio-cognitive apprenticeship theory based on modeling, coaching, scaffolding, articulation, reflection and exploration. Two data collection instruments; observation checklist and semi-structured interviews were used. Interviews were audio-recorded, transcribed and subjected to thematic analysis manually. Credibility was ensured by multiple data collection sources comprising of observation notes, reflective journal and audio-recordings of reflections, coaching sessions and interviews. Results: Total 10 novice PBL facilitators were interviewed. Six themes generated: mental growth spurred from within, conscientization, experiential learning, intrinsic motivation and effective body language and impediment to success. Learning by observation, learning by doing, increased motivation, autonomy, constructive feedback and reflection augmented the facilitation skills. Whereas, unawareness about reflective practices and peer coaching were identified as major obstacles in personal and professional growth of faculty. Conclusion: “Cognitive peer coaching” is a dynamic, innovative and feasible faculty development approach that contributed to the learning of facilitation skills from psychological, emotional and social perspective. It should be implemented by policy makers as a part of ongoing professional development programme. Keywords: Cognitive peer coaching, PBL facilitation, faculty development